The Establishment of a New Autonomous Region of Papua in State Administrative Law Perspective - Jauhar Nashrullah; Georges Olemanu Lohalo (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2022)
The presence of four new autonomous regions (DOB) in Papua completes the number of provinces in Indonesia to 38. This study examines the formation of the new autonomous region in Papua from the perspective of state administrative law. This type of research is juridical normative with a statutory, concept, and case approach. The study results show Law Number 2 of 202,1, which eliminates preparation areas, even though the preparation areas are crucial in forming a new autonomous region. With asymmetric decentralization, special autonomy will be imposed on the new autonomous regions in Papua, which have specificity regarding authority, finance, and institutions. However, there are several notes, such as the Governor and DPRP formed from the results of the 2024 simultaneous elections & regional election; as a result, the acting governor is equipped with crucial authority that is prone to conflict of interest. This article also provides ideas and recommendations regarding the formation of the Papua new autonomous region as follows: 1) The implementation of primary areas in the process of forming the Papua new autonomous region; 2) The government immediately issued government regulation of Desartada; 3) Maximizing the participation of indigenous Papuans in the establishment of the new autonomous region in Papua.